2007
DOI: 10.1590/s1517-83822007000300030
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of most probable number of Salmonella in minced pork samples

Abstract: The quantification of microorganisms present in food samples is an important step to assess the risk to consumers. The number of salmonellae in 20 positive samples of minced pork was determined by the Most Probable Number method. Counts ranging between <3 and 240 cfu.g -1 were found in the analyzed samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 13 publications
0
7
1
Order By: Relevance
“…The experimental quantitative protocol (direct XLT4 plating) applied in this study proved to have a low sensitivity, since only 21.7% of all samples that were positive by the standard Salmonella qualitative protocol (presence/absence) were detected with the quantitative method. Other authors have developed and evaluated other methodologies to quantify Salmonella in samples, such as spiral plate count, hydrophobic membrane filtration, most probable number, and real-time-PCR, reporting sensitivities ranging from 38.8 to 100% (1,6,8,15,24).…”
Section: Resultsmentioning
confidence: 99%
“…The experimental quantitative protocol (direct XLT4 plating) applied in this study proved to have a low sensitivity, since only 21.7% of all samples that were positive by the standard Salmonella qualitative protocol (presence/absence) were detected with the quantitative method. Other authors have developed and evaluated other methodologies to quantify Salmonella in samples, such as spiral plate count, hydrophobic membrane filtration, most probable number, and real-time-PCR, reporting sensitivities ranging from 38.8 to 100% (1,6,8,15,24).…”
Section: Resultsmentioning
confidence: 99%
“…However, PCR-based methods are limited to qualitative determination. Borowsky, Schmidt, and Cardoso (2007) stated that the quantification of microorganisms present in the food samples is important to assess the risk to consumers. Therefore, the most probable number (MPN) method which estimates the number of microorganism based on the probability is incorporated for the quantification of the PCR products (Mantynen, Niemela, Kaijalainen, Pirhonen, & Lindstrom, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Microbiological quantification of SE86 was carried out using the most probable number (MPN) method (Borowsky et al , 2007). …”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that a well characterised pathogenic S. Enteritidis strain (SE86) was involved in many foodborne outbreaks in the State of Rio Grande do Sul (RS), the southernmost state in Brazil (Geimba et al , 2004; Moura et al , 2001; Oelschlaeger, 2010). In addition, SE86 has been reported to undergo acid adaptation, as characterised by: increased acid and thermal resistance (Araya et al , 2010) higher survival rates in simulated gastric fluid (Bernardeau et al , 2008), and better intestinal colonisation in mice (Borowsky et al 2007; Malheiros et al , 2009; Perez et al , 2010). …”
Section: Introductionmentioning
confidence: 99%